The Use of Tutorial Video in Learning Energy Sources - Wahyuni, Ni Luh Putu Indra; Sudatha, I Gde Wawan; Jayanta, I Nyoman Laba (Universitas Pendidikan Ganesha, 2021)
Students' interest in participating in online learning was still low, so learning media is important to increase student interest in online learning. This study aimed to produce audio-visual learning media using the principle of dynamic drawing on 9 sub-theme one science content with the topic of energy and energy sources in grade IV elementary school was valid. This study was development research that was guided by the 4D model procedure. The subjects of this research trial consisted of one material expert, one design expert, and one media expert, three students for individual trials, and nine students for small group trials—the data collected in this study, namely qualitative data and quantitative data. Data were collected using a questionnaire method with the distribution of rating scale instruments. The data analysis method used in this research was to determine the percentage of each respondent. The validity of the science learning videos was determined from expert tests and product trials through learning material expert tests, learning design expert tests, teaching media experts, individual tests, and small group tests. The percentage was 93.6%, with a very good category. So the results showed that learning videos can be declared suitable for science learning for grade IV elementary schools and can explain concrete material.Students' interest in participating in online learning was still low, so learning media is important to increase student interest in online learning. This study aimed to produce audio-visual learning media using the principle of dynamic drawing on 9 sub-theme one science content with the topic of energy and energy sources in grade IV elementary school was valid. This study was development research that was guided by the 4D model procedure. The subjects of this research trial consisted of one material expert, one design expert, and one media expert, three students for individual trials, and nine students for small group trials—the data collected in this study, namely qualitative data and quantitative data. Data were collected using a questionnaire method with the distribution of rating scale instruments. The data analysis method used in this research was to determine the percentage of each respondent. The validity of the science learning videos was determined from expert tests and product trials through learning material expert tests, learning design expert tests, teaching media experts, individual tests, and small group tests. The percentage was 93.6%, with a very good category. So the results showed that learning videos can be declared suitable for science learning for grade IV elementary schools and can explain concrete material.